Putting Low Emission Zone (LEZ) to the Test: The Effect of London's LEZ on Education - Antonio Avila-Uribe; Sefi Roth; Brian Shields (Institute of Labor Economics (IZA), 2024)
This paper evaluates the impact of London's Low-Emission Zone (LEZ) on test scores among elementary school students in England. Utilising administrative data for the years 2005-2015, we employ a difference-in-differences approach to assess the LEZ's effect on standardised Key Stage 2 results (age 11). Our analysis reveals a statistically and economically significant improvement of 0.09 standard deviations in test scores for students within the LEZ compared to those in other urban control areas. Importantly, we also find that the LEZ policy has larger positive effects in low-performing schools, demonstrating its potential to significantly reduce educational disparities.
Keywords: Q53; I20; I24; 330; air pollution; education; low emission zone